Radioisotope-guided Lymphadenectomy for Pelvic Lymph Node Staging in Patients With Intermediate- and High-risk Prostate Cancer (The Prospective SENTINELLE Study). Issue 2 (4th November 2022) - Lannes, François; Baboudjian, Michael; Ruffion, Alain; Rouy, Mathieu; Giammarile, Francesco; Rousseau, Thierry; Kraeber-Bodéré, Françoise; Rousseau, Caroline; Rusu, Daniela; Colombié, Mathilde; Brenot-Rossi, Isabelle; Rossi, Dominique; et al.
Abstract : Purpose: Our aim was to prospectively evaluate the diagnostic accuracy of sentinel lymph node biopsy-guided lymph node dissection compared to extended pelvic lymph node dissection in patients with intermediate- or high-risk prostate cancer. Materials and Methods: We conducted a prospective, single-arm, multicenter study at 3 tertiary centers in France between February 2012 and May 2019. Eligible patients had clinically localized intermediate- or high-risk prostate cancer. After intraprostatic injection of (99m)Tc-nanocolloid, the locations of the sentinel lymph nodes were defined by preoperative lymphoscintigraphy. Surgical excision of the sentinel lymph nodes was performed using intraoperative gamma probe guidance. After resection of the sentinel lymph nodes, extended pelvic lymph node dissection was performed in all patients. We assessed the diagnostic accuracy of the sentinel lymph node biopsy method using extended pelvic lymph node dissection as the reference standard. This trial was registered in ClinicalTrials.gov (NCT02732392). Results: A total of 162 men cN0M0 (CT scan and bone scan) were enrolled: 106 (65.4%) and 56 (34.6%) patients had intermediate- and high-risk prostate cancer, respectively. The median number of nodes retrieved was 14 (mean 16, IQR 10-21) per patient. At final pathological analysis, 22 patients (13.6%) were pN+. Sensitivity, specificity, negative predictive value, and positive predictive value of sentinel lymph node biopsy method in detecting patients with at least 1 lymph node metastasis were 95.4% (95% CI, 75.1-99.7), 100% (95% CI, 96.6-100), 99.2% (95% CI, 95.5-99.9), and 100% (95% CI, 80.7-100), respectively. Conclusions: Our multicenter prospective study supports that sentinel lymph node biopsy is a very effective and sensitive method for pelvic lymph node staging in patients with intermediate- or high-risk localized prostate cancer.